Construcción e instalación de un prototipo para llenado de botellones con agua y su implementación con un controlador lógico programable - Chong Hidalgo, Pablo César (2023)
The target the general of the present thesis was: constructing, installing and implementing with a programmable logical control (PLC), to a prototype for filling of large bottles with water. Coming true ad hoc a revision detailed on the languages more used (ladder and FDB) in the programming of a PLC. Straightaway, came true the diagram ladder and the simulation of the filling of large bottles with water took effect, this in turn allowed determining that the quantity of physical receipts and expenditures that were used in the PLC are: three entrances (I1, I2, and I3) and three physical exits (Q1, Q2 and Q3). At last, came true the performance testings of said prototype, the ones that it was used in three (3) sets of large bottles, with the following nominal volumes: five of 3.8 L, two of 4.5 L and three of 20 L; findings of fact in each case the following times filling: 8.1 s, 9.5 s and 42.4 s, respectively. For the ten used large bottles, it has been determined that the difference trough and peak between the nominal volume and the observed volume are: 0.342 % and 2.000 %, respectively, which did not exceed of the 2 % regarding the nominal volume, being proved this way that the mentioned prototype works of efficient way. Then, it can be said that the present investigation is somewhat diligent, with quantitative focus and i design correlational. In this way the present work of thesis is concluded, coming true with every one of the realistic brand-name drugs and the general objective lens.